KEJAHATAN ELEKTRONIK DALAM TRANSASKSI (FRAUD CYBER CRIME) BURSA EFEK INDONESIA PT DSFI - Azura, Syah Rani; Izari, Izari; Maharani, Sauh Galia (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2021)
Indonesia is one of the countries that is not immune from technological developments. The influence of globalization and free trade, supported by advances in telecommunications and information technology, has expanded the space for the flow of goods transactions entering Indonesia, both legally and illegally. This study aims to analyze the case of Fraud Cyber Crime as a detection tool in the disclosure of electronic transaction crimes in a company listed on the Indonesia Stock Exchange. This research uses a qualitative research approach with the dependent variable and the independent variable. Sources of data obtained from this research are through documentation from the internet and literature study from books and journals. The results of this study are in the form of scope of cyber fraud stim. The legal basis underlying the crime of electronic transactions. detection of PT DSFI cases and prevention of electronic transaction crimes. This study focuses on cases with a type of securities market manipulation that is detrimental to customers. So it can be concluded that the importance of legal protection for victims of Cyber Crime fraud and tight security in a transaction.